Tp63-expressing adult epithelial stem cells cross lineages boundaries revealing latent hairy skin competence - Stéphanie Claudinot (Nature Portfolio, 2020)
Adult stem cells are thought to be fate restricted to lineages distinct to their tissue of origin. Here, the authors demonstrate that Tp63 expressing epithelial stem cells from several disparate tissues can respond to skin morphogenetic signals and contribute to hair follicles, sebaceous glands and/or epidermis.